Great saphenous vein leiomyosarcoma: a rare case report and literature review - Ying Liu; Bin Dong; Chunjie Hou; Litao Sun; Genshan He; Qiaohong Hu (Frontiers in Oncology)
Great saphenous vein leiomyosarcoma is an extremely rare tumor clinically, which is often misdiagnosed as superficial venous thrombosis due to atypical clinical manifestations. This report describes a rare presentation of great saphenous vein leiomyosarcoma in a 37-year-old man who was referred to our hospital due to a gradually enlarging painless mass on his left shank. Ultrasound revealed that the mass in the left calf was a solid tumor originating from the left great saphenous vein. He underwent radical resection for the mass ultimately. Subsequent histopathological and immunohistochemical analyses resulted in a conclusive diagnosis of primary leiomyosarcoma originating from the great saphenous vein. There are only 56 cases of great saphenous vein leiomyosarcoma reported in medical databases worldwide at present, which are summarized and analyzed here.